Negative pole piece and preparation method thereof, battery and electric equipment

By constructing a suitable amorphous carbon clad structure in the negative electrode material of lithium-ion batteries, the ratio of graphitized carbon content and artificial graphite particle size distribution index is controlled, and the problems of active lithium loss and life attenuation of lithium-ion batteries during fast charging and circulation are solved, and excellent fast charging performance, good cycling performance and high-temperature storage performance are achieved.

CN119650587APending Publication Date: 2025-03-18ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411808993.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries have problems of active lithium loss and life attenuation during fast charging and circulation, especially in the poor performance under high temperature conditions.

Method used

By constructing a fast-charging negative electrode active material with a graphitized carbon content suitable for the particle size of the artificial graphite particle powder, the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles is controlled to be within the range of 0.29 to 0.55 to improve the cycle stability and high-temperature performance of the battery.

Benefits of technology

The circulation performance and high-temperature storage performance of the negative electrode active material are significantly improved, and the fast charging performance is optimized, avoiding the loss of active lithium and life attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650587A_ABST
    Figure CN119650587A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece and a preparation method thereof, a battery and electric equipment, and relates to the field of batteries. The negative electrode piece comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises an amorphous carbon coating material and artificial graphite particles. Wherein the ratio of the graphitized carbon content of the amorphous carbon coated material to the particle size distribution index of the artificial graphite particles is 0.29-0.55. According to the invention, the rapid charging performance is relatively excellent, and the cycle performance and the high-temperature storage performance of the power rapid charging type lithium ion battery are both improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a negative electrode plate and a preparation method thereof, a battery and an electrical device. Background Art

[0002] As a new generation of secondary rechargeable batteries, lithium-ion batteries have significant advantages, including high energy density making them lighter and smaller, high discharge rate and low self-discharge rate, no toxic substances such as lead and chromium, and immunity to memory effect. In the process of studying and developing lithium-ion batteries, the research and development of negative electrode materials is the core of improving the performance of lithium-ion batteries. Graphite is widely regarded as one of the most promising negative electrode materials because of its good lithium deintercalation ability and high theoretical capacity (372mAh / g). Therefore, the development of high-power graphite negative electrode materials that can support fast charging and stable cycle performance is crucial to the performance of lithium-ion batteries.

[0003] In the related art, a core-shell graphite-based graphite negative electrode material is constructed by coating. Among them, the coating agent is selected from graphitizable carbon materials or non-graphitizable carbon materials. After the carbonization process, the coating agent can form an amorphous carbon structure on the graphite surface. The amorphous carbon structure has a larger carbon layer spacing than the intrinsic structure of graphite, and is rich in irregularly arranged stacking defect structures, which is conducive to Li+ adsorption and rapid deintercalation.

[0004] However, as the cycle process proceeds, structures such as spiral dislocations and stacking defects in the amorphous carbon layer can easily cause irreversible decomposition of organic solvents on the surface of the carbon negative electrode and solvent co-intercalation, resulting in loss of active lithium and life decay. There is an urgent need to provide a fast-charging lithium-ion battery that can meet the cycle life and high-temperature performance requirements. Summary of the invention

[0005] The present application provides a negative electrode plate and a preparation method thereof, a battery and an electrical device, which can achieve better fast charging performance and improve the cycle performance and high-temperature storage performance of power fast-charging lithium-ion batteries.

[0006] In a first aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector, and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising an amorphous carbon coating material and artificial graphite particles; the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles is 0.29 to 0.55.

[0007] In a possible implementation manner, the graphitized carbon content of the amorphous carbon coating material is 32% to 92%.

[0008] In a possible implementation manner, the graphitized carbon content of the amorphous carbon coating material is 44% to 68%.

[0009] In a possible implementation manner, the particle size distribution index of the artificial graphite particles is 0.75 to 2.0.

[0010] In a possible implementation manner, the particle size distribution index of the artificial graphite particles is 1.12 to 1.42.

[0011] In a possible implementation, the artificial graphite particles include one or more of artificial graphite flakes, artificial graphite blocks, and artificial graphite balls.

[0012] In a possible implementation, the precursor of the amorphous carbon coating material includes one or more of coal tar pitch, tar pitch, coal-based pitch, oil-based pitch, phenolic resin, citric acid, glucose, and soluble starch.

[0013] In a possible implementation manner, the thickness of the amorphous carbon coating layer in the negative electrode active material layer is 20 nm to 500 nm.

[0014] In a second aspect, the present application provides a method for preparing a negative electrode sheet, which is used to prepare the negative electrode sheet provided in the first aspect, and the method for preparing the negative electrode sheet comprises: mixing a negative electrode active material, a conductive material, a thickener, a dispersant, a binder and deionized water to obtain a negative electrode slurry; coating the negative electrode slurry on both sides of the negative electrode collector copper foil, and then drying, rolling and die-cutting to obtain a negative electrode sheet.

[0015] In a possible implementation manner, the mass percentages of the negative electrode active material, the conductive material, the thickener, the binder and the dispersant are 94wt%, 2wt%, 2wt%, 1.5wt% and 0.5wt%, respectively.

[0016] In a possible implementation manner, the solid content of the negative electrode slurry is 30 wt % to 65 wt %; and / or the viscosity of the negative electrode slurry at room temperature is 1000 mPa·s to 8000 mPa·s.

[0017] In a possible implementation manner, the single-side thickness of the coating layer of the negative electrode plate is 0.05 mm to 0.30 mm; and / or the unit area mass of the coating layer is 80 g / m 2 ~200g / m 2 ; and / or, the compacted density of the coating layer is 1.30g / cm 3 ~1.75g / cm 3 .

[0018] In a third aspect, the present application provides a battery, comprising a negative electrode plate, a positive electrode plate, an electrolyte and a separator as provided in the first aspect.

[0019] In a fourth aspect, the present application provides an electrical device, comprising a battery as provided in the third aspect.

[0020] The implementation of this application has at least the following beneficial effects:

[0021] 1) By constructing a fast-charging negative electrode active material with a suitable graphitized carbon content of the amorphous carbon coating layer and the particle size of the artificial graphite particle powder, the cycle stability and high temperature performance of the battery are improved;

[0022] 2) The inventors have found that under the same conditions of amorphous carbon coating, the ideal graphitized carbon content of amorphous carbon and the particle size distribution of artificial graphite particles have a great influence on the electrochemical performance of the negative electrode sheet. By controlling the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles in the negative electrode active material to 0.29-0.55, the cycle performance of the negative electrode active material can be significantly improved. That is, only by controlling the ideal graphitized carbon content on the surface of the amorphous carbon coating material and the particle size parameters of the artificial graphite particles, without adjusting the graphitization degree, specific surface area, powder OI value, sphericity parameters, coating layer thickness, pore volume and porosity of the negative electrode active material, a fast-charging amorphous carbon-coated graphite negative electrode material can be obtained, which has both excellent cycle performance and high-temperature storage performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the structure of a negative electrode active material provided in one embodiment of the present application;

[0024] Figure 2 A schematic diagram of the structure for performing Gaussian peak fitting processing on the diffraction peak of graphite carbon 002 provided in one embodiment of the present application.

[0025] Explanation of the reference numerals: 1: amorphous carbon coating material; 2: artificial graphite; 3: local short-range disordered γ peak; 4: local short-range ordered π peak; 21: graphite carbon 002 diffraction peak; 22: short-range disordered γ peak; 23: short-range ordered π peak. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the scheme of the present application, the present application is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present application, and the examples cited are only used to explain the present application, and are not intended to limit the scope of the present application. Based on the embodiments of the present application, all other implementation methods obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.

[0027] When graphite is applied to fast-charge lithium-ion batteries, graphite negative electrodes still face certain technical problems. These technical problems mainly include the narrow gaps in the graphite layer structure (0.335nm), which hinders the diffusion of lithium ions in graphite and affects its ideal charge and discharge rate performance; when lithium ions are embedded, they need to enter the material from the edge of the layer along a longer path, which limits the rate performance of the battery; during fast charging, the polarization phenomenon of graphite will make it close to the deposition potential of lithium metal, which may lead to surface lithium precipitation and the formation of lithium dendrites, which not only weakens the battery performance, but also may cause internal short circuit or thermal runaway; because the graphite sheets are held together by weak van der Waals forces, the instability of the structure may cause the sheets to be co-embedded with solvent molecules when lithium ions are embedded, resulting in the peeling and shedding of the sheets, further affecting the electrochemical performance. Therefore, the development of high-power graphite negative electrode materials that can support fast charging and have stable cycle performance is crucial to the performance of lithium-ion batteries.

[0028] In the related art, a core-shell graphite-based graphite negative electrode material is constructed by coating. Among them, the coating agent selects easily graphitized carbon material or difficultly graphitized carbon material. The coating agent can form an amorphous carbon structure on the graphite surface after the carbonization process. The amorphous carbon structure has a larger carbon layer spacing than the intrinsic structure of graphite, and is rich in irregularly arranged stacking defect structures, which is conducive to Li+ adsorption and rapid deintercalation. However, as the cycle process proceeds, structures such as spiral dislocation and stacking defects in the amorphous carbon layer are prone to irreversible decomposition and solvent co-intercalation of organic solvents on the surface of the carbon negative electrode, resulting in loss of active lithium and life attenuation. It is urgent to provide a fast-charging lithium-ion battery that can meet the cycle life and high temperature performance.

[0029] Based on the technical problems existing in the related art, the embodiments of the present application can realize a negative electrode active material with excellent fast charging performance, cycle performance and high temperature performance by controlling the graphitized carbon content of the amorphous carbon coating outer layer in the negative electrode active material and the powder particle size grading of the inner core of the graphite particles.

[0030] An embodiment of the present application provides a negative electrode plate, comprising: a negative electrode current collector, and a negative electrode active material layer arranged on at least one side surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising an amorphous carbon coating material and artificial graphite particles; the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles is 0.29 to 0.55.

[0031] The present application does not particularly limit the composition of the negative electrode current collector, which can be selected from negative electrode current collectors commonly used in the art, such as copper foil.

[0032] For example, the negative electrode active material provided in the embodiment of the present application may be a core-shell structure, that is, an amorphous carbon-coated outer layer and an artificial graphite particle inner core structure.

[0033] Exemplarily, the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles can be expressed by the following formula:

[0034] 0.29≤Ig / S≤0.55

[0035] Wherein, Ig represents the graphitized carbon content of the amorphous carbon coating material, and S represents the particle size distribution index of the artificial graphite particles.

[0036] For example, the graphitized carbon content of the amorphous carbon coating material may be an ideal graphitized carbon content of the amorphous carbon coating material.

[0037] Exemplarily, the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles can be 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55 or a range consisting of any two of them.

[0038] In a specific embodiment, the graphitized carbon content of the amorphous carbon coating material is obtained by testing with a grazing incidence XRD tester, and further by standard card comparison, XRD refinement and analysis. The calculation formula of the graphitized carbon content of the amorphous carbon coating material can be expressed by the following formula:

[0039] Ig=Aπ / (Aπ+Aγ)

[0040] Wherein, Aπ is the peak area of ​​π peak obtained by Gaussian peak fitting of the diffraction peak of graphite carbon 0 0 2, and Aγ is the peak area of ​​γ peak obtained by Gaussian peak fitting of the diffraction peak of graphite carbon 0 0 2.

[0041] According to the inventor's research, the ideal graphitized carbon content of the amorphous carbon coating material can be obtained based on the ratio of the π peak area to the γ peak area, and the defect distribution density of the amorphous carbon coating layer can be obtained accordingly.

[0042] In a specific embodiment, the particle size distribution index of the artificial graphite particles is obtained by a laser diffraction particle size analyzer (MS3000). The particle size distribution index of the artificial graphite particles can be expressed by the following formula:

[0043] S=(D90-D10) / D50

[0044] Here, D90 represents a particle size at 90% of the volume-based cumulative particle size distribution, D10 represents a particle size at 10% of the volume-based cumulative particle size distribution, and D50 represents a particle size at 50% of the volume-based cumulative particle size distribution.

[0045] It can be understood that the particle size distribution index of the artificial graphite particles can reflect the concentration of the artificial graphite particles.

[0046] The inventors have found through extensive research that when the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles in the negative electrode active material is within the range of 0.29 to 0.55, the negative electrode active material has a better surface carbon layer structure, and its long-range ordered and short-range disordered amorphous carbon coating structure has a reasonable interlayer spacing, a moderate defect density, and is rich in lithium insertion active sites. The negative electrode active material has a better surface carbon layer structure, which is specifically reflected in the microcrystalline parameters of the negative electrode active material, that is, the amorphous carbon coating material tends to have an ideal graphite carbon content value within the ideal range. At the same time, the powder particle size of the artificial graphite particles of the negative electrode active material can achieve particle size matching, and the narrow particle distribution can reduce the frequency of fine powder and large particles. The particle size distribution is concentrated and the microcrystalline parameters of the coating layer make the negative electrode active material have a higher kinetic ability of lithium removal and lithium insertion. After disassembling the battery cell pole piece, there is no lithium precipitation phenomenon on its surface. At the same time, its cycle retention rate and capacity retention rate are significantly improved. This shows that by controlling the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles to 0.29-0.55, the orientation degree of the negative electrode active material is higher, the extreme disorganized structure and the invalid lithium insertion structure are reduced, and the excessive decomposition of the electrolyte at high temperature causing the loss of active lithium and active materials is avoided, thereby achieving better battery kinetic performance and good high temperature storage performance and cycle performance.

[0047] Figure 1 This is a schematic diagram of the structure of the negative electrode active material provided in one embodiment of the present application. Figure 1 As shown, the negative electrode active material includes an amorphous carbon coating material 1 and artificial graphite particles 2, that is, the negative electrode active material is an amorphous carbon coating outer layer and an artificial graphite particle inner core structure. Among them, the microcrystalline parameters of the amorphous carbon coating material 1 include a local short-range disordered γ peak 3 and a local short-range ordered π peak 4.

[0048] Exemplarily, the crystallite parameters of the amorphous carbon coating material 1 are obtained by performing XRD characterization on the negative electrode active material and performing Gaussian peak fitting processing on the graphite carbon 002 diffraction peak in the XRD data obtained by the characterization.

[0049] Figure 2 This is a schematic diagram of a structure for performing Gaussian peak fitting processing on the graphite carbon 002 diffraction peak provided in an embodiment of the present application. Figure 2As shown, the horizontal axis represents the X-ray scanning range, and the vertical axis represents the diffraction peak intensity at different diffraction angles. By performing Gaussian peak fitting on the graphite carbon 002 diffraction peak 21, the short-range disordered γ peak 22 and the short-range ordered π peak 23 can be separated, and the γ peak area and the π peak area can be obtained, and the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material can be further obtained.

[0050] In a specific embodiment, the graphitized carbon content of the amorphous carbon coating material is 32% to 92%.

[0051] Exemplarily, the graphitized carbon content of the shaped carbon coating material may be 32%, 36.2%, 51.9%, 55.4%, 56.2%, 68.8%, 82.6%, 91.6%, 92%, or a range consisting of any two thereof.

[0052] In a preferred embodiment, the graphitized carbon content of the amorphous carbon coating material is 44% to 68%.

[0053] For example, the graphitized carbon content of the shaped carbon coating material may be 44%, 51.9%, 55.4%, 56.2%, 68%, or a range consisting of any two thereof.

[0054] The inventors have found that the ideal graphitized carbon content of the amorphous carbon coating material is an important indicator for measuring the defect density of the amorphous carbon coating layer. The higher the ideal graphitized carbon content, the higher the regularity of the amorphous carbon coating structure, the closer the amorphous carbon coating layer spacing and the amorphous carbon coating structure are to the ideal graphite crystal structure, and the fewer defect structures lead to relatively fewer end-face active sites, so the loss of active lithium at high temperatures is less, and the battery using the amorphous carbon coating material has better cycle performance and storage performance at high temperatures. The lower the ideal graphitized carbon content of the amorphous carbon coating material, the structure of its amorphous carbon coating layer points to a chaotic layer graphite structure in the form of Sp2 hybridization, the higher the defect density, the larger the amorphous carbon coating layer spacing, the richer the lithium insertion active sites, and the better the fast charging performance, but due to its surface pore structure and chaotic layer structure, the loss of active lithium during circulation and storage is more serious.

[0055] In this application, the powder parameters and physical and chemical properties of the negative electrode active material are accurately identified by using a grazing incidence XRD diffractometer to construct a fast-charging graphite negative electrode material that meets the performance requirements of the power battery from the powder level.

[0056] In a specific embodiment, the particle size distribution index of the artificial graphite particles is 0.75-2.0.

[0057] Exemplarily, the particle size distribution index of the artificial graphite particles can be 0.75, 0.80, 0.85, 0.90, 0.95, 1.05, 1.1, 1.15, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range consisting of any two thereof.

[0058] In a preferred embodiment, the particle size distribution index of the artificial graphite particles is 1.12 to 1.42.

[0059] Exemplarily, the particle size distribution index of the artificial graphite particles can be 1.12, 1.13, 1.14, 1.15, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.30, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1.38, 1.39, 1.40, 1.41, 1.42 or a range consisting of any two thereof.

[0060] The inventors have found that the powder particle size distribution index of artificial graphite particles can be used to describe the aggregation degree of the graphite active material powder particle size. The corresponding parameters such as the powder particle size distribution index of artificial graphite particles can be obtained by performing particle size frequency statistics on the negative electrode active material powder particle size through a laser particle size distribution instrument. Low concentration of the negative electrode active material powder particle size indicates that the artificial graphite particle size distribution is wide, the size difference of the negative electrode active material is large, there are fine powders and oversized particles, etc. The large specific surface area of ​​the fine powder is easy to cause high temperature performance deterioration, and the surface defect degree distribution density of the oversized particle negative electrode active material is uneven. Under the influence of fast charging, the nucleation overpotential of the surface defect position is too low, causing local lithium precipitation, thereby causing irreversible lithium generation, and thus its high temperature performance and fast charging performance are deteriorated. Therefore, by adjusting the content and distribution of fine powder and large particles by grading the powder particle size, the cycle retention rate and storage capacity of fast-charging graphite can be improved.

[0061] In a specific embodiment, the artificial graphite particles include one or more of artificial graphite flakes, artificial graphite blocks, and artificial graphite balls.

[0062] In a specific embodiment, the precursor of the amorphous carbon coating material includes one or more of coal tar pitch, tar pitch, coal-based pitch, oil-based pitch, phenolic resin, citric acid, glucose, and soluble starch.

[0063] Exemplarily, the coal-based asphalt may include medium-temperature coal-based asphalt and high-temperature coal-based asphalt.

[0064] Exemplarily, the oil-based asphalt may include medium-temperature oil-based asphalt and high-temperature oil-based asphalt.

[0065] In a specific embodiment, the thickness of the amorphous carbon coating layer in the negative electrode active material layer is 20 nm to 500 nm.

[0066] Illustratively, the thickness of the amorphous carbon coating layer in the negative electrode active material layer may be 20 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, or a range consisting of any two thereof.

[0067] The inventors have found that in the related technologies, due to the influence of characterization accuracy and other factors, the surface and interface parameters of the amorphous carbon-coated artificial graphite in the negative electrode active material have not been focused on. In the present application, the crystallite parameters of the amorphous carbon coating material layer in the negative electrode active material are accurately characterized and analyzed, and a grazing incidence XRD diffractometer is used to adjust its test parameters to accurately anchor the test range to 20nm to 500nm on the surface of the negative electrode active material powder. The amorphous carbon coating layer structure is finely scanned, and the XRD data obtained by characterization are further refined and analyzed by mathematical means to identify the crystallite parameters of the amorphous carbon coating layer structure, that is, the ideal graphitized carbon content of the amorphous carbon coating material. Then, through a large number of experiments, they are associated with the macroscopic parameters of the negative electrode active material powder to construct the structure-activity relationship between the crystallite parameters of the amorphous carbon coating layer and the negative electrode active material powder indicators and the electrical performance of the full battery using the negative electrode active material, thereby obtaining a fast-charging artificial graphite negative electrode material that meets the current needs of power batteries.

[0068] The present application also provides a method for preparing a negative electrode sheet, which is used to prepare the negative electrode sheet as described above. The method for preparing the negative electrode sheet comprises: mixing a negative electrode active material, a conductive material, a thickener, a dispersant, a binder and deionized water to prepare a negative electrode slurry; coating the negative electrode slurry on both sides of a negative electrode collector copper foil, and then drying, rolling and die-cutting to obtain a negative electrode sheet.

[0069] The present application does not particularly limit the type of conductive material, which can be selected from conductive agents commonly used in the art, including but not limited to one or more of carbon black, graphene, carbon fiber and carbon nanotubes.

[0070] The present application does not particularly limit the type of thickener, which can be selected from thickeners conventionally used in the art, including but not limited to one or more of sodium carboxymethyl cellulose, polyvinyl alcohol, xanthan gum, polyacrylic acid and hydroxypropyl methylcellulose.

[0071] The present application does not particularly limit the type of dispersant, which can be selected from dispersants conventionally used in the art, including but not limited to one or more of polyvinyl pyrrolidone, sodium polyacrylate, sodium carboxymethyl cellulose and polyethylene glycol.

[0072] The present application does not particularly limit the type of binder, which can be selected from binders conventionally used in the art, including but not limited to one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol and polyurethane.

[0073] In a preferred embodiment, the mass percentages of the negative electrode active material, the conductive material, the thickener, the binder and the dispersant are 94wt%, 2wt%, 2wt%, 1.5wt% and 0.5wt%, respectively.

[0074] In a specific embodiment, the solid content of the negative electrode slurry is 30wt% to 65wt%;

[0075] Illustratively, the solid content of the negative electrode slurry may be 30 wt %, 35 wt %, 40 wt %, 45 wt %, 50 wt %, 55 wt %, 60 wt %, 65 wt % or a range consisting of any two thereof.

[0076] In a specific embodiment, the viscosity of the negative electrode slurry at room temperature is 1000 mPa·s to 8000 mPa·s.

[0077] Exemplarily, the viscosity of the negative electrode slurry at room temperature may be 1000 MPa·s, 1500 MPa·s, 2000 MPa·s, 2500 MPa·s, 3000 MPa·s, 3500 MPa·s, 4000 MPa·s, 4500 MPa·s, 5000 MPa·s, 5500 MPa·s, 6000 MPa·s, 6500 MPa·s, 7000 MPa·s, 7500 MPa·s, 8000 MPa·s or a range consisting of any two thereof.

[0078] In a specific embodiment, the single-side thickness of the coating layer of the negative electrode plate is 0.05 mm to 0.30 mm;

[0079] Illustratively, the single-sided thickness of the coating layer of the negative electrode sheet may be 0.05 mm, 0.10 mm, 0.15 mm, 0.20 mm, 0.25 mm, 0.30 mm, or a range consisting of any two of them.

[0080] In a specific embodiment, the mass per unit area of ​​the coating layer is 80 g / m 2 ~200g / m 2 ;

[0081] For example, the mass per unit area of ​​the coating layer may be 80 g / m 2 , 90g / m 2 , 100g / m 2 , 110g / m 2, 120g / m 2 , 130g / m 2 , 140g / m 2 , 150g / m 2 , 160g / m 2 , 170g / m 2 , 180g / m 2 , 190g / m 2 , 200g / m 2 Or a range consisting of any two of them.

[0082] In a specific embodiment, the compacted density of the coating layer is 1.30 g / cm 3 ~1.75g / cm 3 .

[0083] For example, the compacted density of the coating layer may be 1.30 g / cm 3 , 1.35g / cm 3 , 1.40g / cm 3 , 1.45g / cm 3 , 1.50g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 , 1.75g / cm 3 Or a range consisting of any two of them.

[0084] The present application also provides a battery, comprising the negative electrode plate, the positive electrode plate, the electrolyte and the isolation membrane as described above.

[0085] An embodiment of the present application also provides an electrical device, comprising the battery as described above.

[0086] The present application does not specifically limit the electronic device, which may be any electrical device including the battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, and energy storage devices.

[0087] The negative electrode plate and battery provided by the present application will be described in detail below through specific embodiments.

[0088] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0089] Example 1

[0090] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is as follows:

[0091] 1. Preparation of negative electrode sheet

[0092] It should be noted that the negative electrode active material in the present application, namely the amorphous carbon coated material and the artificial graphite particles, can be obtained by grading and screening commercial negative electrode materials. The negative electrode slurry is prepared by screening suitable amorphous carbon coated artificial graphite negative electrode active materials.

[0093] Add negative electrode active material, conductive material, thickener, dispersant, binder and deionized water to a stirring tank, stir for 2 hours at a revolution speed of 25r / min to form a mixed negative electrode slurry, evenly coat the negative electrode slurry on both sides of the negative electrode current collector copper foil, dry in an oven, and then obtain negative electrode sheets after cold pressing and slitting. Among them, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is 0.39, the thickness of the amorphous carbon coating layer is 40nm, the mass percentages of the negative electrode active material, the conductive material, the thickener, the binder and the dispersant are 94wt%, 2wt%, 2wt%, 1.5wt% and 0.5wt% respectively, and the solid content of the negative electrode slurry is 35wt% to 65wt%.

[0094] 2. Preparation of positive electrode

[0095] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O. A conductive agent such as conductive carbon black and a binder such as polyvinylidene fluoride are mixed uniformly in a proper amount of solvent NMP according to a mass ratio of 96:2:2 to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on both sides of the positive electrode current collector aluminum foil, and then dried, rolled, and die-cut to obtain a positive electrode sheet.

[0096] 3. Preparation of electrolyte

[0097] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after full dissolution.

[0098] 4. Preparation of isolation membrane

[0099] A polyethylene film with an aluminum oxide coating was selected as the separator.

[0100] 5. Preparation of batteries

[0101] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order so that the separator is between the positive electrode sheet and the negative electrode sheet, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and the battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0102] Exemplarily, the battery may be a lithium-ion battery.

[0103] Example 2

[0104] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.56.

[0105] Example 3

[0106] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.20.

[0107] Example 4

[0108] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.46.

[0109] Example 5

[0110] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.37.

[0111] Example 6

[0112] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.32.

[0113] Example 7

[0114] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.68.

[0115] Example 8

[0116] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.39, and the thickness of the amorphous carbon coating layer is 62 nm.

[0117] Example 9

[0118] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.23, and the thickness of the amorphous carbon coating layer is 18 nm.

[0119] Example 10

[0120] This embodiment provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.42, and the thickness of the amorphous carbon coating layer is 97 nm.

[0121] Comparative Example 1

[0122] This comparative example provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 1.25.

[0123] Comparative Example 2

[0124] This comparative example provides a negative electrode plate and a battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the negative electrode plate, the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is replaced with 0.14.

[0125] Test Case

[0126] 1. Characterization of graphitized carbon content of amorphous carbon coating materials

[0127] The XRD diffraction spectrum of the amorphous carbon coating layer was obtained by grazing incidence XRD diffractometer testing. The negative electrode active material powder sample was evenly dispersed on the surface of the optical glass plate, and the sample measurement parameters were adjusted so that the X-ray scanning depth was the thickness of the amorphous carbon coating layer (the thickness of the amorphous carbon coating layer can be obtained by TEM microscope) to avoid excessive detection depth leading to interference of the signal in the core of the artificial graphite particles.

[0128] Test method: incident angle 0.5°, working voltage 40kV, working current 40mA, scanning range 15-35°, step length 0.02°, then compare the diffraction pattern with the standard card, Gaussian peak fitting of the graphite carbon 00 2 diffraction peak (26°) to obtain the γ peak and π peak, the π peak area ratio is the ideal graphitized carbon content of the amorphous carbon coating material, the number of scanned samples is 10, and the arithmetic mean is the ideal graphite carbon content of the amorphous carbon coating layer.

[0129] It should be noted that the thickness of the amorphous carbon coating layer is associated with the residual carbon content. For example, when the thickness of the amorphous carbon coating layer is 40 nm, the corresponding residual carbon content is 2%, when the thickness of the amorphous carbon coating layer is 62 nm, the corresponding residual carbon content is 3.6%, when the thickness of the amorphous carbon coating layer is 18 nm, the corresponding residual carbon content is 1.0%, when the thickness of the amorphous carbon coating layer is 97 nm, the corresponding residual carbon content is 5.4%, etc.

[0130] 2. Characterization of particle size distribution index of artificial graphite particles

[0131] By using a laser diffraction particle size analyzer (MS3000), the sample particles are dispersed in a liquid medium at a concentration of 200mg / L to 300mg / L, and a monochromatic light beam is passed through. After the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values ​​of the scattering diagram at many angles and records these values ​​for analysis. Using the Rayleigh scattering formula, the scattering values ​​are calculated to obtain the ratio of the volume of particles of each particle size level to the total volume, thereby obtaining the volume distribution of the particle size. The particle size distribution index can reflect the concentration of artificial graphite particles.

[0132] 3. Lithium ion battery lithium deposition test

[0133] Test method: At 25°C, the lithium-ion battery prepared in the embodiment and the comparative example was fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium-ion battery was fully charged at a 4C rate, and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, the area of ​​lithium deposition on the surface of the negative electrode is less than 10% is considered as slight lithium deposition, the area of ​​lithium deposition is 10-50% is considered as moderate lithium deposition, and the area of ​​lithium deposition is greater than 50% is considered as severe lithium deposition.

[0134] 4. Lithium-ion battery cycle performance test

[0135] Test method: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were charged at a 1C rate and discharged at a 1C rate, and a full charge-discharge cycle test was performed, and the 1000cls capacity retention rate was recorded.

[0136] 5. Lithium-ion battery high temperature storage performance test

[0137] Test method: At 60°C, the lithium-ion batteries prepared in the implementation examples and comparative examples were subjected to 0.33C capacity calibration to obtain a capacity of Cn1; then placed in a high-temperature oven, taken out after 56 days and subjected to 0.33C capacity calibration at room temperature to obtain a capacity of Cn2, and the residual capacity rate = Cn2 / Cn1*100%.

[0138] Table 1 shows the parameters corresponding to the embodiments and comparative examples provided in this application.

[0139] Table 1

[0140]

[0141] Table 2 Performance test results of lithium-ion batteries

[0142] Table 2

[0143]

[0144]

[0145] The following conclusions can be drawn from Table 1 and Table 2:

[0146] 1) By comparing the performance test results of the embodiments and comparative examples, it can be seen that when the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles Ig / S is in the range of 0.29 to 0.55, the lithium-ion battery has better kinetic performance and has good high temperature and cycle performance. This is due to the fact that the negative electrode active material provided in the present application has a better surface carbon layer structure, and its long-range ordered and short-range disordered amorphous carbon coating structure has a reasonable interlayer spacing, a moderate defect density, and is rich in lithium insertion active sites, which is specifically reflected in the microcrystalline parameters of the negative electrode active material, that is, the amorphous carbon coating material tends to have an ideal graphite carbon content value within an ideal range. At the same time, the powder particle size of the artificial graphite particles of the negative electrode active material can achieve inter-particle grading, and the narrower particle distribution can reduce the frequency of fine powder and large particles. The particle size distribution is concentrated and the microcrystalline parameters of the coating layer make the negative electrode active material have a higher kinetic ability of lithium removal and lithium insertion. After disassembling the battery cell electrode, there is no lithium precipitation phenomenon on its surface. At the same time, its cycle retention rate and capacity retention rate are significantly improved. This shows that by controlling the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles to 0.29-0.55, the orientation degree of the negative electrode active material is higher, the extreme disorganized structure and the invalid lithium insertion structure are reduced, and the excessive decomposition of the electrolyte at high temperature causing the loss of active lithium and active materials is avoided. The combination of its surface and interface microscopic parameters and active material powder indicators can achieve better battery kinetic performance, as well as good high temperature storage performance and cycle performance.

[0147] 2) When the ratio of the graphitized carbon content of the amorphous carbon coating material in the negative electrode active material to the particle size distribution index of the artificial graphite particles is too low or exceeds the lower limit, as shown in the above Example 3 and Comparative Example 2, the cycle performance and storage performance of the lithium-ion battery are poor. This is because the amorphous carbon coating layer tends to have an ideal graphitized carbon content that is too low, the carbon layer spacing on the surface of the amorphous carbon is too large, the surface disordered structure and defect density are too high, and Li+ is not easily deintercalated effectively to form dead lithium during the cycle, and the too wide particle size distribution makes the powder rich in fine powder and large particles. The fine powder of artificial graphite particles has a high specific surface area and the electrochemical activity causes excessive decomposition of the electrolyte. The large-particle artificial graphite has a long lithium insertion path, and the surface nucleation overpotential is unevenly distributed under fast charging conditions to form lithium precipitation. Not only is the capacity loss serious during the cycle and storage process, but its dynamics are also deteriorated.

[0148] 3) When the ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles in the negative electrode active material is too high or exceeds the upper limit, as shown in the above-mentioned Example 7 and Comparative Example 1, this indicates that the ideal graphitized carbon content on the surface of the amorphous carbon coating layer is too high, the structure of the amorphous carbon coating layer is regular and the orientation degree is reduced. Although its cycle life and high-temperature storage performance are improved, the spacing between its amorphous carbon coating layers is closer to the carbon layer spacing of the artificial graphite core, which is not conducive to the rapid deintercalation of lithium ions. Therefore, its dynamics are significantly deteriorated, and slight or even severe lithium precipitation occurs at the disassembled electrode interface, which cannot meet the ultra-fast charging requirements of lithium-ion power batteries.

[0149] 4) Examples 8-10 show the effect of the thickness of the amorphous carbon coating. Compared with Example 5, when the thickness of the amorphous carbon coating is high, as shown in Examples 8 and 10, the lithium-ion battery exhibits higher kinetic performance, but the high-temperature storage performance is weakened, which indicates that the amorphous carbon coating is easy to deteriorate at high temperatures when the thickness is large; in Example 9, the thickness of the amorphous carbon coating is designed to be 18nm, and because the graphite powder particle size distribution is too wide, it is not conducive to the material kinetics, so the amorphous carbon coating of the material is difficult to meet the rate requirements of ultra-fast graphite charging of lithium-ion batteries.

[0150] In summary, when designing amorphous carbon-coated graphite negative electrode materials, by making the microcrystalline parameters of the amorphous carbon coating layer of the negative electrode active material and the particle size distribution of the graphite negative electrode material powder within a reasonable range, it is possible to achieve higher kinetic performance of lithium removal and lithium insertion, while making lithium ions have both better cycling performance and storage performance.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A negative electrode plate, characterized in that: include: A negative electrode current collector, and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises an amorphous carbon coating material and artificial graphite particles; The ratio of the graphitized carbon content of the amorphous carbon coating material to the particle size distribution index of the artificial graphite particles is 0.29 to 0.

55.

2. The negative electrode sheet according to claim 1, characterized in that: The graphitized carbon content of the amorphous carbon coating material is 32% to 92%.

3. The negative electrode sheet according to claim 2, characterized in that: The graphitized carbon content of the amorphous carbon coating material is 44% to 68%.

4. The negative electrode sheet according to claim 1, characterized in that: The particle size distribution index of the artificial graphite particles is 0.75-2.

0.

5. The negative electrode sheet according to claim 4, characterized in that: The particle size distribution index of the artificial graphite particles is 1.12 to 1.

42.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The artificial graphite particles include one or more of artificial graphite flakes, artificial graphite blocks and artificial graphite balls.

7. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The precursor of the amorphous carbon coating material includes one or more of coal tar pitch, tar pitch, coal-based pitch, oil-based pitch, phenolic resin, citric acid, glucose, and soluble starch.

8. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The thickness of the amorphous carbon coating layer in the negative electrode active material layer is 20nm to 500nm.

9. A method for preparing a negative electrode sheet, characterized in that: For preparing the negative electrode sheet according to any one of claims 1 to 8, the preparation method of the negative electrode sheet comprises: Mixing the negative electrode active material, the conductive material, the thickener, the dispersant, the binder and the deionized water to prepare a negative electrode slurry; The negative electrode slurry is coated on both sides of the negative electrode current collector copper foil, and then dried, rolled and die-cut to obtain the negative electrode sheet.

10. The method for preparing a negative electrode sheet according to claim 9, characterized in that: The mass percentages of the negative electrode active material, the conductive material, the thickener, the binder and the dispersant are 94 wt %, 2 wt %, 2 wt %, 1.5 wt % and 0.5 wt % respectively.

11. The method for preparing a negative electrode sheet according to claim 9, characterized in that: The solid content of the negative electrode slurry is 30wt% to 65wt%; And / or, the viscosity of the negative electrode slurry at room temperature is 1000 mPa·s to 8000 mPa·s.

12. The method for preparing a negative electrode sheet according to claim 9, characterized in that: The single-side thickness of the coating layer of the negative electrode plate is 0.05 mm to 0.30 mm; And / or, the mass per unit area of ​​the coating layer is 80 g / m 2 ~200g / m 2 ; And / or, the compaction density of the coating layer is 1.30 g / cm 3 ~1.75g / cm 3 .

13. A battery, characterized in that: It comprises a negative electrode sheet, a positive electrode sheet, an electrolyte and a separator as described in any one of claims 1 to 8.

14. An electrical device, characterized in that: Comprising the battery of claim 13.